Spectroscopical Investigation of Human Grown Urinary Calculi in and Around Puducherry Region - Vijayaprasath R; Selvaraju R; Renuka Devi K.B (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Urinary calculi taken from patients in the Southern Indian area of Pondicherry are spectroscopically analysed in this study. The chemical content, molecular structure and categorization of 20 urinary stone samples are ascertained by the use of complementary Ultraviolet – Visible (UV-Vis) and Fourier Transformer – Infrared (FTIR) spectroscopy methods. FT-IR analysis confirmed the presence of specific functional groups associated with Calcium oxalate, Calcium phosphate, Uric acid, Struvite and mixed composition. UV spectroscopy revealed distinctive absorption patterns between 200-400nm providing initial identification of stone type. According to the results the majority of the people under study had calcium oxalate (62%) followed by the uric acid (19%), calcium phosphate (11%), struvite (6%) and mixed composition (2%). A quick, accurate and non-destructive analytical tool for the clinical diagnosis and epidemiological evaluation of urolithiasis in the area is provided by this dual Spectroscopical technology. The Scanning Electron Microscopy (SEM) analysis shows the morphology of the collected samples. The result offer important information for creating treatment plans and targeted prevention measures tailored to the urolithiasis patterns seen in the Pondicherry community.
Keywords: Urolithiasis; Calcium oxalate; Uric acid; FT-IR; SEM